Rancang Bangun Alat Deteksi Masker, Deteksi Suhu Badan dan Sprayer Disinfektan Sebagai Pendisiplin Protokol Kesehatan Di Lingkungan Sekolah - Anang Habibi; Fadhillah Aris Ramadhan Ginting; Royyan Putra Prasetyo (Universitas Halu Oleo, 2022)
COVID-19 has swept the world for almost two years. The increase in COVID-19 cases is caused by the lack of public compliance with health protocols. Schools are places where teachers and students gather; some schools in certain zones are permitted by the government to carry out teaching and learning activities face-to-face but still under strict health protocols. Parents are still worried that their children will catch COVID-19 at school because of the school community's neglect of health protocols; robots play an important role in reducing the chain of COVID-19 cases. Through this research, the authors innovate by using cameras to help monitor school residents to comply with health protocols in wearing masks, infrared sensors for hand detection when washing hands and MLX90614 sensors to measure body temperature so that those who do not adhere to the health protocol disciplinary tools are not allowed to enter the school area.